Development of Contextual Learning Design Based on Newman's Diagnosis in Junior High School Fraction Material - Via Arik Kusuma; Nawal Ika Susanti (SIMFONI: Jurnal Sains dan Sosial Multidisipliner, 2026)
The digital era demands strong mathematical literacy, yet students often encounter significant obstacles with fractions, particularly in word problems. This study aimed to develop a contextual learning design integrating the Newman Diagnosis to analyze and enhance the mathematical literacy of female junior high school students regarding fraction operations. Employing the Research and Development (R&D) method based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved 34 seventh-grade female students from SMP Plus Darussalam. Data collection involved preliminary observation, expert validation, pre-tests, post-tests, and an analysis of error patterns using the Newman model. The results demonstrated that the learning design—comprising a teaching module and Student Activity Sheets (LAS) structured according to the Newman framework—possessed very high validity (validation scores ranging from 81.82% to 90.91%). Implementation of the product proved effective in significantly improving mathematical literacy, evidenced by an increase in the mean score from 18.03 (pre-test) to 37.56 (post-test) and a moderate N-Gain category across all literacy indicators. Error analysis revealed that the students' errors were concentrated primarily in the Transformation (47.45%) and Process Skills (46.86%) stages, while error rates in the Reading (17.25%) and Comprehension (17.25%) stages were comparatively low. It is concluded that integrating Contextual Teaching and Learning (CTL) with the Newman Diagnosis successfully addressed systematic conceptual barriers, established a coherent problem-solving flow, and tangibly fostered students' mathematical literacy regarding fractions.